Removal of locked intramedullary nails with the aid of bolts - Echem, Richard C.; Eyimina, Phillip D. (International Journal of Research in Medical Sciences, 2020)
Background: Removal of an intramedullary nail would require the extraction system of the inserted nail to be available. Sometimes the system is not available, and an alternative system would have to be utilised. Aim of the study was to document the removal of interlocked nails using bolts in the absence of appropriate fitting extraction system. Methods: A prospective study of consecutive patients seen by the authors between September 2016 and September 2018 in private clinics in Port Harcourt where the authors were invited to remove intramedullary nails. Bolts fitted to the proximal tips of the nails were utilized. With the aid of plier applied to the bolts and mallet, the nails were extracted. The patients’ socio-demographic and information relevant to the injury were obtained. Data was analysed using SPSS version 23. Results: Fifteen patients were seen. Ages ranged from 29 to 72 years, consisting of 10 males and five females. The tibia was affected in six and the femur in nine. There were five united tibial fractures and one non-united tibial fracture, six united femoral fractures and three non-united femoral fractures. Indication for removal was mostly patients’ request. Duration of surgery ranged from 1 to 4 hours. All the nails were extracted. Complications included broken nail, heterotopic calcification, bony overgrowth/ ingrowth/ongrowth around the nail and interlocking screws. There was no mortality. Conclusions: In the absence of conventional intramedullary nail extraction system, appropriate size bolts can be applied to the threaded proximal tip of nails and used for nail extraction.